How Can Samapta Patrol Prevent Criminal Acts of Theft? - Herawati, Veronica Ari; Wijaya, I Wayan Widia (Faculty of Law, Universitas Negeri Semarang, 2023)
The surge in aggravated theft in Tegal Regency has spurred unease among its residents, prompting the National Police to proactively address the issue through patrols conducted by the Tegal Police Samapta Unit. This study employs qualitative approaches and field research to assess the optimization of Samapta patrols in preventing aggravated theft at the Tegal Police Station. Key conceptual literature encompasses optimization, aggravated theft, crime prevention, patrol strategies, and management theory. The research reveals that aggravated theft predominantly occurs at night, featuring methods such as damaging doors, windows, and ternity. To enhance Samapta patrols, the study advocates prioritizing dialogical patrols. Optimization involves implementing dialogical strategies, conducting patrols collaboratively with rank-and-file police, involving personnel from other units, and utilizing innovations like the Galawi Traffic Management Command Center (GTMCC). Additionally, introducing reward and punishment programs is proposed. Internal factors hindering optimization include inadequate personnel quantity and quality, insufficient budgetary support for fuel and vehicle repairs, monotonous beat routes, and misaligned patrol targets with the evolving nature of theft crimes. External factors involve the lack of coordination with related functions and community collaboration to bolster patrol efficacy. Consequently, the current implementation of Samapta patrols by the Tegal Police falls short of optimal prevention against aggravated theft.